ARSITEKTUR KESEHARIAN DALAM TIPOLOGI GALERI SENI DI SETIABUDI, JAKARTA - Philip Efraim; DIah Anggraini (Jurusan Arsitektur dan Perencanaan, 2022)
Jakarta has been the 9th most stressful city in the world with the highest stress index placing right after Kiev, Ukraina. According to survey in one of the company based in Jakarta, 80% of the staff confessed had a pressured work environment either the cause was work demands, unfriendly environment, or personal problems. In the other hand, art has been part of human civilization from the start until now. Art has been involved in human’s daily life, reached every aspect of human’s life quality. Few researches have stated that art has a part in human’s learning process and sharpen the human’s cognitive system. Based on the facts of the current circumstances, this study was made to create and develop a design concept of Art Gallery which holds a part in being a space for self healing for the urban society. The merge of these functions was based on the process of re-thinking of the typology of Art Gallery in general also by adding daily architecture approah in the design process. Keywords: Art Gallery; Art; Daily Architecture; Self-healing; StressAbstrakKota Jakarta merupakan kota dengan kedudukan ke-9 setelah Kiev, Ukraina sebagai kota dengan indeks stres terbesar di dunia. Menurut hasil survey di salah satu perusahaan di Jakarta, 80% karyawannya mengaku stres dengan pekerjaannya, akibat tuntutan pekerjaan, lingkungan kerja, dan masalah individu. Sementara itu, seni adalah bagian dari kehidupan manusia sejak awal peradabannya hingga sekarang. Seni terlibat dalam kehidupan sehari-hari manusia, dalam semua aspek kehidupan manusia. Beberapa penelitian juga menyebutkan bahwa seni bisa membantu proses belajar manusia dan melatih sistem kognitif manusia. Mengacu pada kondisi tersebut, maka studi ini bertujuan menghasilkan suatu konsep perancangan galeri seni yang sekaligus dapat menjadi wadah self healing bagi warga kota. Penggabungan kedua fungsi ini dilandasi dengan proses berpikir ulang terhadap tipologi galeri pada umumnya juga menambahkan pendekatan arsitektur keseharian dalam proses perancangan.